P01.03 RNAi mediated PD-1 knockdown induces a TCF-1 positive population in activated human CD8 T cells with stem-like associated marker profile. (21st September 2022) - Herbstritt, AS; Maxwell, M; Yan, D; Cuiffo, B; Cardia, J; Zhou, S; Fricker, SP; Noessner, E
Abstract : Background: Adoptive Transfer of antigen specific T cells (ATT) is a powerful tool in the treatment of cancer. However, there are still hurdles to satisfactory efficacy. 1 One of them is the upregulation of immune-inhibitory receptors like programmed cell death protein 1 (PD-1). Silencing PD-1 at the mRNA level would not only prevent expression and therefore the inhibitory interaction with its ligand PD-L1, but also inhibit tonic signalling. 2 This should increase proliferation, cytotoxicity, cytokine production and metabolic activity via the AKT pathway. Another well-known hurdle to ATT efficacy is the poor persistence of effector T cells in patients. Stem-like memory subsets of CD8 T cells such as those marked by TCF-1 expression may therefore represent an advantageous effector population for ATT, as they show longer persistence, higher proliferative activity, responsiveness to checkpoint inhibitors and the ability to differentiate into new effector T cells. 3 Increasing the proportion of this population is thought to be beneficial in anti-tumor therapy. Here, we present data showing that specific downregulation of PD-1 using a novel RNA interference (RNAi) technology increases the frequency of a CD8 T cell population with a stem-like associated marker profile. Materials and Methods: INTASYL™ compounds incorporate drug-like properties into RNAi, resulting not only in enhanced cellular uptake but also eliminates the need for transfection reagents. TCR53-transduced T cells, suitable for ATT, were incubated with PD-1 targeting INTASYL compound PH-762 for 24h. As controls, cells were either treated with a non-targeting compound (NTC) or left untreated (UTC). Following PH-762 loading, T cells were co-cultured with the autologous tumor cell line RCC-53 for 96h. PD-1 knockdown efficacy was assessed along with other markers of interest via flow cytometry before and after co-culture. Results: PH-762 treatment reduced PD-1 surface expression in TCR53 T cells after 24h by ~50% compared to UTC or NTC. PH-762 mediated PD-1 silencing increased the subset of TCF-1 positive T cells at 24h post compound treatment and continued through 96h of co-culture with tumor cells. The TCF-1 positive cells expressed stem-like markers including higher expression levels of CD127 and CCR7 together with CD95 and lower levels of perforin. Conclusions: Increasing the proportion of stem-like CD8 T cells holds promise for optimizing ATT. PD-1 knockdown in TCR53 CD8 T cells for ATT by PH-762 induced the emergence of a T cell population expressing stem-like phenotypic markers including TCF-1. Further experiments are underway to assess the effects of the induced stem-like properties on a functional level, including proliferative activity and effector cell differentiation. References: Sterner RC, Sterner RM. CAR-T cell therapy: current limitations and potential strategies. Blood Cancer J 2021;11 (4):69. Fernandes RA, Su L, Nishiga Y, et al . Immune receptor inhibition through enforced phosphatase recruitment. Nature 2020;586 (7831):779–84. Siddiqui I, Schaeuble K, Chennupati V, et al . Intratumoral Tcf1+PD-1+CD8+ T Cells with Stem-like Properties Promote Tumor Control in Response to Vaccination and Checkpoint Blockade Immunotherapy. Immunity 2019;50 (1):195–211.e10. Disclosure Information: A.S. Herbstritt: C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Significant; Phio Pharmaceuticals. M. Maxwell: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. D. Yan: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. B. Cuiffo: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. J. Cardia: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. S. Zhou: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. S.P. Fricker: A. Employment (full or part-time); Significant; Phio Pharmaceuticals. E. Noessner: C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Significant; Phio Pharmaceuticals.